Seasonal Water Footprint Assessment For A Paint Industry Wastewater Treatment Plant - Pelin Yapıcıoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Paint manufacturing industries have many unfavorableenvironmental impacts such as freshwater consumption. Especially, paintindustry wastewater treatment plants consume huge water volumes. Waterfootprint is described as the total volume of water required for a concept. The main aim of the studyis to determine the seasonal variation of water footprint for a full-scalepaint industry wastewater treatment plant which locates in Turkey. Grey waterfootprint was evaluated by Water Footprint Network methodology. Chemical OxygenDemand (COD), Total Suspended Solids (TSS) and Oil and Grease (O&G) are thepollutant parameters to detect it. Water consumption of the plant containssludge treatment, process water usage and other residential activities aredefined as the component of blue water footprint. According to the results,maximum grey water footprint was measured in May as the value of 2455.840352 m3.month-1.The least total grey water footprint is related to August as 536.7118464 m3.month-1. Total blue water footprintis 4866.9 m3.year-1 and the peak value is 421.7 m3.month-1in March. According to the study, thegrey water footprint is higher than blue footprint. The results reveal that fordecreasing water footprint, COD removal efficiency should be increased andwastewater reuse alternatives should be implemented.